Information asymmetry, trading volume and returns in the Malaysian stock market - Chue, Wen Yeen; Lai, Ming Ming (2007)
This paper examines investors’ motive to trade on the Malaysian stock market from 1st July 1997 to 30th June 2005. By applying ordinary least square (OLS) to 272 stocks as well as in three size groups, both the time series and cross-sectional results indicate that speculation on firm specific asymmetric information is the primary motive to trade on Malaysian stock market for the full and two sub-sample periods. The results show that most of the investors in Malaysian stock market tend to speculate firm related information to maximize their profits. The findings of this study provide important implications to policy makers in addition to investors in this developing market. Proper management of foreign portfolio investment is crucial to prevent manipulative moves and excessive speculative forms of portfolio investments that may cause excessive surges of inflows and massive panic outflows of short-term capital and thus collapse the financial system and downturn economy.